Two Transcription Products of the Vesicular Stomatitis Virus Genome May Control L-Cell Protein Synthesis - Dunigan, David D. (1983)
When mouse L-cells are infected with vesicular stomatitis virus, there is a decrease in the rate of protein synthesis ranging from 20 to 85% of that in mock-infected cells. Vesicular stomatitis virus, irradiated with increasing doses of UV light, eventually loses this capacity to inhibit protein synthesis. The UV inactivation curve was biphasic, suggesting that transcription of two regions of the viral genome is necessary for the virus to become inactivated in this capacity. The first transcription product corresponded to about 373 nucleotides, and the second corresponded to about 42 nucleotides. Inhibition of transcription of the larger product by irradiating the virus with low doses of UV light left a residual inhibition of protein synthesis consisting of approximately 60 to 65% of the total inhibition. This residual inhibition could be obviated by irradiating the virus with a UV dose of greater than 20,000 ergs/mm(2) and was thus considered to represent the effect of the smaller transcription product. In the R1 mutant of C. P. Stanners et al. (Cell 11:273-281, 1977), inhibition of transcription of the larger product sufficed to restore protein synthesis to the mock-infected level, suggesting that the smaller transcription product is nonfunctional with respect to protein synthesis inhibition. It thus appears that the inhibition of protein synthesis by wild-type vesicular stomatitis virus involved at least two separate viral transcription products, and the inhibition by the R1 mutant involved only one. Extracts from cells infected with virus irradiated with low doses of UV light showed a protein synthesis capacity quite similar to that of their in vivo counterparts, indicating that these extracts closely reflect the in vivo effects of virus infection.